Post-menopausal osteoporosis: prevalence of risk factors and probable symptoms - Bhatia, Manohar; Mishra, Ashok; Sukla, Pradeep (International Journal Of Community Medicine And Public Health, 2018)
Background: Osteoporosis jeopardizes the quality of life of many post-menopausal women due to its sequelae of fractures on trivial trauma. With a rapid increase in average life expectancy India is becoming home to a huge population at risk of osteoporosis. The aims and objectives of the study were to assess the prevalence of fractures due to trivial trauma and probable symptoms of osteoporosis and prevalence of modifiable and non-modifiable risk factors of osteoporosis in postmenopausal women Methods: A cross-sectional study, conducted by a door to door survey in 400 post-menopausal women (below 65 yrs) in urban Gwalior city from September to December 2012. The risk factors of osteoporosis in post-menopausal women have been classified into modifiable and non-modifiable risk factors. Modifiable risk factors include exercise/physical activity and consuming milk and milk products while age of menarche, age of menopause, reproductive period and parity were categorized as non-modifiable risk factors. Results: In our study, the overall prevalence of osteoporotic symptoms was 62.75% (251/400). Out of 400 postmenopausal women, 45.25% had backache, 55.75% had joint pain and 24.00% had fractures. Prevalence of osteoporotic fractures was much higher (39.16%) in females not consuming milk and milk products & in females who never exercised (35.22%). 60% of females who underwent hysterectomy had osteoporotic fractures. Conclusions: The overall prevalence of osteoporotic fractures among post-menopausal females was higher in our study when compared to other studies in the same setting. Thus, a multipronged approach involving educational intervention, lifestyle modification and appropriate hormonal treatment is required. Lifestyle modification involves nutritional interventions and motivation for regular physical activity.